O envelhecimento da população brasileira e seus desafios - Moser, Antônio (Revista eclesiástica brasileira, 2010)
Demography presents itself as a complex reality that must be assessed from multiple angles. The fact is, although there are still some areas in Brazil where there is a predominance of young faces, the country is beginning to worry about other faces: those of its sixteen million inhabitants who are over 60. It is obvious that a greater longevity must be greeted as a positive thing. However, this positivity will only be real when longevity is combined with quality of life. And quality of life is the result of various personal and social factors. Hence the logical consequence that, at the same time that quality of life demands personal efforts, it also requires social efforts to make available better social, economic and political conditions to all. The present study intends to show that, as in so many other aspects of personal and social life, nothing happens by chance. Everything depends on long and continuous work. Through it people and societies will gradually learn to administer their gifts and also their limitations. Successful ageing is a synonym of wisdom in living and of clever public policies.